p53 expression in colorectal tumors. - Purdie, C. A. (1991)
The expression of the nuclear phosphoprotein p53 was studied immunohistochemically in a series of 150 benign and malignant colorectal tumors. Using monoclonal antibody PAb1801, tumors divided unequivocally into two groups on the basis of immunohistochemistry. Forty of the carcinomas (46.5%) showed positive staining but only 4 of the adenomas (8.7%) were positive (P less than 0.001). The few positive adenomas always showed moderate or severe dysplasia. Metaplastic polyps (n = 9) and small familial adenomatous polyposis-related adenomas (n = 9) were uniformly negative. Carcinomas with p53 expression did not differ from those without in terms of site, differentiation or the prognostic indicators of Dukes' stage, DNA ploidy, or tumor histology. The improved morphologic resolution available in periodate lysine paraformaldehyde dichromate (PLPD)-fixed, paraffin-embedded tissue permitted several conclusions to be made: p53 is confined to neoplastic nuclei; staining in positive tumors is heterogeneous and often more marked at the infiltrative margins; and staining intensity is dramatically reduced in mitotic cells. It is concluded that expression of immunohistochemically detectable p53 (probably representing mutated forms of the protein) occurs in some adenomas around the time of transition to carcinoma. Therefore there is an association with the appearance of infiltrative behavior but not with degree of tumor progression (including metastasis) at the time of resection.